P61 The Prevalence of Childhood Overweight and Obesity in the Republic of Ireland in 2002 and 2014. (13th September 2016) - McCarthy, LE; Harding, M; Geaney, F; Kelleher, V; Perry, I
Abstract : Background: The prevalence of overweight and obesity appears to have reached a plateau across many developed countries, including Ireland. The aim of this review was to examine the 12-year trend of the prevalence of overweight and obesity among primary school aged children in the Republic of Ireland between 2002 and 2014. Methods: BMI data from two representative cross-sectional samples of school-going children (age range 3–14 years) was analysed from 2002 (n = 14, 054) and 2014 (n = 5, 232). Data on height and weight were objectively measured by trained research assistants in 2002 from a random sample (based on age, gender and geographical location of school) using standardised and calibrated measures. These Methods were replicated for data collection conducted in 2014. Standard International Obesity Task Force criteria was applied to determine the prevalence of overweight and obesity. Results: Between 2002 and 2014, the prevalence of overweight and obesity has decreased from 23% (95% CI: 22.3% to 24.3%) to 20% (95% CI: 18.8% to 21.9%) among boys and from 29% (95% CI: 27.5% to 29.6%) to 27% (95% CI: 24.9% to 28.3%) among girls aged 4–13 years in the Republic of Ireland. Among children in Junior Infants (3–7 year olds), the prevalence of overweight and obesity has decreased from 22% (95% CI: 20.7% to 23.5%) to 18% (95% CI: 15.8% to 19.7%) among boys and 29% (95% CI: 27.0% to 30.2%) to 25% (95% CI: 23.0% to 27.5%) among girls, while among children in 6 th class (9–14 year olds), the prevalence has decreased from 25% (95% CI: 23.0% to 27.0%) to 23% (95% CI: 21.2% to 26.0%) for boys but has increased from 26% (95% CI: 24.5% to 28.4%) to 28% (95% CI: 25.8% to 30.9%) among girls. Conclusion: These results are consistent with a slight fall in the prevalence of overweight and obesity among younger and older children in the Republic of Ireland. While these findings are encouraging, overall prevalence remains high and the issue of childhood overweight and obesity must remain a key public health policy issue.